Creación de una heladería en base a crema y queso en la ciudad Latacunga, parroquia Belisario Quevedo. - Duque Mora, Lady Estefania (2022)
Entrepreneurship is a choice to innovate, launch our own ideas, grow economically and promote a better quality of life by creating jobs, and partially solve unemployment. The objective of this project is to determine the feasibility for the creation of an ice cream parlor in the city of Latacunga, Belisario Quevedo parish, aimed at people from 5 to 34 years of age. The purpose is to offer ice cream of different flavors with cream and cheese in attractive presentations, in a place themed with ice cream figures and playgrounds. A market study was carried out to know aspects of tastes and preferences of customers' ice cream consumption. The business model was applied through the CANVAS canvas to have the central idea of the business. In addition, with the help of the tools of the 5 forces of PORTER and PEST, the threats and opportunities of the project are determined. The initial investment needed to start the business is $6,215.08, which will be financed 25% with its own capital and 75% through a five-year debt with a bank. Finally, a financial analysis was constructed where a NPV of $969.78, IRR of 15.23% and a WACC of 9.24% were obtained, demonstrating the viability of the project, which, when executed, will offer personal growth and sources of employment that by thus improves the economic development of the Parish.